Comparison of the Effect of Lidocaine and Ketamine on Prevention of Fentanyl-Induced Cough during the Induction of Anesthesia in Children under General Anesthesia - Amir Shafa; Mohamadreza Habibzadeh; Negin Goodarzi (مجله دانشکده پزشکی اصفهان, 2019)
Background: One of the main adverse effects of fentanyl, as the most commonly used anesthetic drug in children, is coughing. Several medications have been used to reduce this complication. In this study, the effect of ketamine and lidocaine on cough reduction after fentanyl injection was investigated.